Variaciones estacionales e históricas de las especies ícticas de la laguna Chascomús - Berasain, Gustavo E. (2006)
In the last five decades the ictiofauna of Chascomús Shallow lake has been studied in quite detail. Between 1999 and 2000 monthly samples of fish with fyke nets were taken. Thus obtaining the cuali-quantitative composition of each sample taken. These were used to assess the variations between sites and seasons of the year. Among the 17 species caught Porteño, pejerrey and sabalito were present in all the samples taken, wichwere dominant and wich represented 51%, 24% and 14% of the total number respectively, and 28% 10% and 37% in weight. Their composition was similar in all stations sampling at every date. Notwithstanding this differences between abundance (CPUEn) and the extracted biomass (CPUEw) were observed. The capture by unit of total effort decreased from winter to autumn. The average (CPUEw) for Chascomús was above the values corresponding to 47 samples taken in different water bodies from Buenos Aires pampas. Comparing the results with the obtained historical data throughout 40 years it was observed that the percentage of the planctophagous species, pejerrey and mandufia marked a declining tendency. On the other handthe biomass of the porteño and sabalito showed a market increase. Significant correlations between these changes and the antropogénic impact were observed.